Injectable self-crosslinking HA-SH/Col I blend hydrogels for in vitro construction of engineered cartilage. (15th June 2018) - Chen, Yafang; Sui, Junhui; Wang, Qing; Yin, Yijia; Liu, Jun; Wang, Qiguang; Han, Xianglong; Sun, Yong; Fan, Yujiang; Zhang, Xingdong
Graphical abstract: Synthesis process and biocompatibility evaluation of thiol modified hyaluronic acid (HA-SH)/Col I blend hydrogels. Highlights: The injectable blend hydrogels with collagen I and thiolated hyaluronic acid could realize unique phase transition behavior in situ from sol to gel in few seconds. The blend hydrogels alleviated collagen I contraction caused by cell traction in vitro and overcame the problem of weak cell adhesion on hyaluronic acid. Chondrocytes encapsulated in Col I7 HA-SH3 blend hydrogel presented most excellent cell proliferation potential and homogeneous distribution. Abstract: The injectable self-crosslinking blend hydrogel by combination of collagen I and thiolated hyaluronic acid could alleviate collagen I contraction in vitro and overcome weak cell adhesive sites of hyaluronic acid. Five groups of injectable hydrogels with different ratios were prepared to investigate their gelation time, injection force, mechanical properties, swelling capacity and disintegration performance. These results indicated that Col7 HA-SH3 hydrogel achieved the optimal controlled and injectable effect, the gelation time was just ten seconds with injection force at 3.5 N, and the storage modulus of hydrogel could reach 11 kPa with frequency at 10 Hz. Furthermore, the phenotype maintaining, biocompatibility and chondrocytes proliferation were administrated by CLSM, SEM, histological staining, immuohistochemical staining, MTT test and glycoaminoglycans quantification. Similarly, the Col7 HA-SH3 blend hydrogel encapsulated chondrocytes presented most excellent proliferation potential, phenotype maintaining, biocompatibility and convenient operational characteristics. These findings might approach the underlying clinical application of blend hydrogel in cartilage repair.